A Literature Review on Public Leadership in Organizations - Asim Ali; Taha Shabbir; Waqar Ali (International Journal of Educational Administration, Management, and Leadership, 2022)
The purpose of this study is to analyze the literature on public leadership, to identify emerging methods to research within that discipline, and to recommend potential research directions for the future. Our attention is focused on organisational leadership from the perspective of the PA, as opposed to other types of public leadership, such as political, community, and military leadership, which are discussed elsewhere. While conducting a literature review and analysis of public leadership, this research makes use of a new mix of bibliometric methodologies that have never been used before. The four basic approaches to public leadership (specifically, "functionalism," "behavioralism," "biography," and "reformism"), each with a distinct philosophy of science (viz., "objective vs. subjective") and the degree of analysis employed (i.e., "high vs. low"), are identified by our results (i.e. micro-level vs multi-level). Following our results, we propose four areas for future investigation: shifting the emphasis away from the "leading" component of public leadership, moving from basic to complicated, and concentrating on public leadership as a starting point for further investigation. A combination of co-citation analysis and bibliographic coupling are the two general bibliometric retrieval approaches that we have employed in our methodology for retrieval.